Exploring the effect of ultramicropore distribution on gravimetric capacitance of nanoporous carbons. (10th June 2018) - Barczak, Mariusz; Elsayed, Yehya; Jagiello, Jacek; Bandosz, Teresa J.
Abstract: The capacitive performance of activated carbons of similar volume of ultramicropores but of marked differences in their pore size distributions was tested in aqueous electrolytes. Dramatic differences in the capacitive behavior were measured in H2 SO4, KOH, or in Na2 SO4 . In the case of the carbon activated with CO2, the sterical hindrances limited the access of Na + ions to pores resulting in a small capacitance. The results indicated that even though the high volume of micropores is required for a good capacitive behavior, it is not a sufficient condition for granting a high capacitance. It was found that even subtle differences in the ultramicropore distribution can affect dramatically the capacitive behavior and, for a given carbon, the electrolyte type needs be adjusted, if the optimum performance is targeted. That adjustment should be made based on the size of the large ion and its compatibility/similarity with/to the predominant ultramicropore size. Carbon surface chemistry does not play a marked role for carbons with a high degree of microporosity when used as supercapacitor electrodes. Since the size of pores are critical for ion accessibility, it is suggested that enhanced adsorption potential in small pore might also contribute to the high capacitive performance in pores similar in size to ions. Graphical abstract: